2019
DOI: 10.48550/arxiv.1908.04942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reinforcement Learning Based Graph-to-Sequence Model for Natural Question Generation

Yu Chen,
Lingfei Wu,
Mohammed J. Zaki

Abstract: Natural question generation (QG) is a challenging yet rewarding task, that aims to generate questions given an input passage and a target answer. Previous works on QG, however, either (i) ignore the rich structure information hidden in the word sequence, (ii) fail to fully exploit the target answer, or (iii) solely rely on cross-entropy loss that leads to issues like exposure bias and evaluation discrepancy between training and testing. To address the above limitations, in this paper, we propose a reinforcemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Recently, GNNs (Hamilton, Ying, and Leskovec 2017;Li et al 2015;Kipf and Welling 2016;Xu et al 2018) have become a hot research topic since their strengths in learning structure data. Various applications in different domains such as chemistry biology (Duvenaud et al 2015), computer vision (Norcliffe-Brown, Vafeias, andParisot 2018), natural language processing (Xu et al 2018;Chen, Wu, and Zaki 2019b) have demonstrated the effectiveness of GNNs. In program scenario, compared with the early works to represent programs with abstract syntax tree (Alon et al 2018(Alon et al , 2019Liu et al 2020b), more works have already attempted to use graphs (Allamanis, Brockschmidt, and Khademi 2017) to learn the semantics for various applications, e.g., source code summarization (Liu et al 2020a;Fernandes, Allamanis, and Brockschmidt 2018), vulnerability detection (Zhou et al 2019), type inference (Allamanis et al 2020).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, GNNs (Hamilton, Ying, and Leskovec 2017;Li et al 2015;Kipf and Welling 2016;Xu et al 2018) have become a hot research topic since their strengths in learning structure data. Various applications in different domains such as chemistry biology (Duvenaud et al 2015), computer vision (Norcliffe-Brown, Vafeias, andParisot 2018), natural language processing (Xu et al 2018;Chen, Wu, and Zaki 2019b) have demonstrated the effectiveness of GNNs. In program scenario, compared with the early works to represent programs with abstract syntax tree (Alon et al 2018(Alon et al , 2019Liu et al 2020b), more works have already attempted to use graphs (Allamanis, Brockschmidt, and Khademi 2017) to learn the semantics for various applications, e.g., source code summarization (Liu et al 2020a;Fernandes, Allamanis, and Brockschmidt 2018), vulnerability detection (Zhou et al 2019), type inference (Allamanis et al 2020).…”
Section: Related Workmentioning
confidence: 99%
“…In addition, many existing graph-based works (Zhou et al 2019;Liu et al 2020a;Fernandes, Allamanis, and Brockschmidt 2018) in program learning have proved the effectiveness of GNNs (Kipf and Welling 2016;Allamanis, Brockschmidt, and Khademi 2017) on capturing program semantics. Furthermore, due to the powerful relation learning capacity of GNNs, they have also been widely used in many NLP reasoning applications, e.g., natural question generation (QG) (Chen, Wu, and Zaki 2019b;Su et al 2020), conversational machine comprehension (MC) (Chen, Wu, and Zaki 2019a;Song et al 2018;De Cao, Aziz, and Titov 2018). Annervaz et al (Annervaz, Chowdhury, and Dukkipati 2018) further proved that augmenting graph information with LSTM can improve the performance of many NLP applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of GNNs [27,15,17,33,58], there is a line of research on developing robust GNNs that are invulnerable to adversarial graphs by leveraging attention-based methods [5], Bayesian methods [13,59] and graph diffusion-based methods [29]. Recently, researchers have explored methods to automatically construct a graph of objects [42,8,32,14] or words [37,6,7] when applying GNNs to non-graph structured data. However, these methods merely optimize the graphs towards the downstream tasks without the explicit control of the quality of the learned graphs.…”
Section: Related Workmentioning
confidence: 99%
“…Another potential reason is that real-world graphs are often noisy or even incomplete due to the inevitably error-prone data measurement or collection. Furthermore, many applications such as those in natural language processing [7,53] may only have sequential data or even just the original feature matrix, requiring additional graph construction from the original data matrix.To address these limitations, we propose an end-to-end graph learning framework, namely Iterative Deep Graph Learning (IDGL), for jointly and iteratively learning the graph structure and the GNN parameters that are optimized towards the downstream prediction task. The key rationale of our ˚Corresponding author.Preprint.…”
mentioning
confidence: 99%
See 1 more Smart Citation